2008
DOI: 10.1182/blood-2007-06-096438
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid inhibits Th17 polarization and enhances FoxP3 expression through a Stat-3/Stat-5 independent signaling pathway

Abstract: IntroductionImmune responses are orchestrated by subsets of CD4 ϩ helper and effector T cells. Classically, differentiated T cells have been classified as belonging either to T-helper 1 (Th1) or Th2 lineages. 1 Th1 cells secrete interferon-gamma (IFN-␥) in response to interleukin-12 (IL-12) and require the transcription factors T-box21 (T-bet) and signal transducer and activator of transcription 4 (Stat4) 2 and Stat1, whereas Th2 cells secrete IL-4, IL-5, and IL-13 and require the transcription factors GATA-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
338
5
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(364 citation statements)
references
References 45 publications
13
338
5
8
Order By: Relevance
“…52 Vitamin A deficiency results in immune dysfunction via excessive IFN-c production and impaired antibody responses. A recent study reported that atRA inhibits Th17 cell differentiation but promotes Foxp3 1 Treg cells, 17,18,53 although the role of atRA in CD4 1 and CD8 1 iTreg cell differentiation may be different. 21 The orphan nuclear receptor, RORct, has been implicated in the gene transcription of Th17 cells.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Vitamin A deficiency results in immune dysfunction via excessive IFN-c production and impaired antibody responses. A recent study reported that atRA inhibits Th17 cell differentiation but promotes Foxp3 1 Treg cells, 17,18,53 although the role of atRA in CD4 1 and CD8 1 iTreg cell differentiation may be different. 21 The orphan nuclear receptor, RORct, has been implicated in the gene transcription of Th17 cells.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
“…16,17 Additionally, atRA promotes the development and function of CD4 1 iTreg cells, although its effect on CD8 1 iTreg cells is minimal. [18][19][20][21] Moreover, atRA also helps preserve nTreg cell stability under inflammatory conditions. 22,23 In this review, we summarize our understanding of the role of atRA in Treg cell biology, its related molecular mechanisms and potential clinical application for patients with autoimmune diseases and who need organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…This employs all-trans retinoic acid (ATRA) where it has been reported that ATRA inhibits TH17 polarisation and enhances Foxp3 expression in CD4 þ T cells. 81,82 Others have shown that ATRA promotes in vivo expansion of Foxp3 þ Tregs associated with suppression of INFg-producing T cells, though without affecting TH17 cells. 83 Recently reviewed by Noelle, 84 ATRA is a nuclear hormone that binds the retinoic acid receptor (RAR, for example, RARa) to form an active transcription factor complex able to activate homeotic genes.…”
Section: Lif As a Therapy For Msmentioning
confidence: 99%
“…85 In development, endogenous ATRA is required for homeostasis in the immune system and for gut homing of T lymphocytes and their increased expression of Foxp3. As ATRA promotes the Treg lineage, 81,82,84,[86][87][88] it is worth asking, is there any evidence for cross-regulation between ATRA and LIF? Importantly, LIF influences oxidative conversion of vitamin A to ATRA in mouse embryonic stem cell; 89 also, LIF synergises with ATRA in differentiation of neural precursor cells to astrocytes 90 and ATRA induces LIF expression in oligodendrocytes: 91 furthermore LIF is induced by ATRA in mouse embryonic stem cell.…”
Section: Lif As a Therapy For Msmentioning
confidence: 99%
“…This is especially relevant in the gut environment where, upon encountering commensal bacteria, dendritic cells secrete proinflammatory cytokines. High concentrations of TGF-β, together with retinoic acid (RA), may be required for induction of Foxp3 + Tregs to suppress potentially detrimental inflammatory Th17 cell responses [57][58][59][60][61][62]. The inhibition of IL-6 receptor (IL-6Rα) expression by RA, suggested by a recent study, provides at least in part an explanation for how RA antagonizes Th17 cell differentiation [63].…”
Section: In Vivo Relevance and Implicationsmentioning
confidence: 99%